The Spiritual Solution of the QanᾹ’ah Hadith to Reduce the Fear of Missing Out (FOMO) in the Digital Era - Sailatul Farhah (Taqriri: Journal of Al-Hadith Science Studies, 2026)
This research aims to discuss the solution offered by the Qana’ah hadith in mitigating Fear of Missing Out (Fomo). This study employs a qualitative approach using the method of interpreting the Qana’ah hadith as a solution to suppress the Fear of Missing Out (Fomo) phenomenon. The results and discussion in this study reveal that Fear of Missing Out, often termed (Fomo), is a symptom of social anxiety arising from the fear of missing out on information, trends, or social activities, especially those spread through digital media. Fomo also impacts mental health, encourages consumptive behavior, and reduces individual satisfaction and inner peace. In this context, the value of Qana’ah (the attitude of feeling content and being pleased with the sustenance granted by Allah) can be used as a spiritual solution to mitigate the Fomo phenomenon, which is the objective of this study. This research concludes that the interpretation of the Qana’ah hadith regarding the Fear of Missing Out (Fomo) phenomenon can be used as a spiritual solution or as a remedy for the Fear of Missing Out (Fomo) ailment.